UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA DENGAN PENDEKATAN METAKOGNITIF PADA MATERI PECAHAN KELAS VII MTs NEGERI BATANG TORU - Himmasari . .; KMS M Fauzi (Universitas Negeri Medan, 2015)
AbstractThis study aims to determine the increase in mathematical problem solving ability of students and student activities on the material fractions with metacognitive approach in class VII MTs Batang Toru. Subjek in this study were students of class VII MTs Batang Toru with many students of 30 people and the object of this study is improve the ability of mathematical problem solving and student activities through the application of metacognitive approach to the material fractions. After administration of the act of learning with metacognitive approach to problem solving ability test results on material obtained fractions in the first cycle of students who understand the problem 90% (very good), students are able to plan troubleshooting 66, 7% (bad), the students were able to solve the problem 63, 3% (bad), and the students were able to examine the returns of 56, 6% (very bad). The results of the study on the second cycle obtained by students who understand the problem 100% (very good), students are able to plan troubleshooting 86, 7% (good), the students were able to solve the problem of 83, 3% (good), and the students were able to re-examine 83, 3% (good) already meets the performance indicators. Conclusion The application of metacognitive approach can improve students' mathematical problem solving at a fraction of material in class VII MTs Batang Toru. Keywords : Classroom Action Research, Mathematical Problem Solving Ability Of Students, Metacognitive Approach.